CO38 | Management of pregnancy, delivery, and postpartum in Italian carriers and women with hemophilia A and B (Bleeding, Thrombosis and Vascular Biology)
Background and Aims: Pregnancy management of carriers/women with hemophilia has four main objectives: preconception and prenatal care, reduction of maternal bleeding, choice of mode of delivery to reduce fetal/neonatal bleeding, and postpartum care. The optimal factor VIII/IX level at the time of delivery and the mode of delivery to reduce maternal and fetal complications are still debated. The aim of this study is to share real-world clinical management in Italian hemophilia treatment centers.